Framing Law and Crime : An Interdisciplinary Anthology. - Picart, Caroline Joan "Kay" S.; Jacobsen, Michael Hviid; Greek, Cecil; Machura, Stefan; Yar, Majid; Boyd, Susan; Menkel-Meadow, Carrie; Kamir, Orit.; Robson, Peter; Deflem, Mathieu (Blue Ridge Summit : Fairleigh Dickinson University Press, 2016)
With contributions by many of the most prominent scholars in law, sociology, criminology, and film, Framing Law and Crime offers a critical survey of a variety of genres and media, integrating descriptions of technique with critical analyses.
Intro -- Contents -- Acknowledgments -- Introduction -- PartI. CINEMATIC HISTORIES AND REAL/REEL DYSTOPIAS OF LAW AND CRIME -- Ch01. Law and Cinema Movement -- Ch02. The Crisis of Law and the Imaginary of Disaster -- Ch03. A Canadian Perspective on Documentary Film -- PartII. JURISPRUDENCE IN INTERNATIONAL FILMS -- Ch04. In The Land of Blood and Honey -- Ch05. Multifocal Judgment, Intersecting Legal Proceedings, and Conservativism -- Ch06. Beyond the Courtroom -- PartIII. LAW AND CRIME IN AMERICAN FILM AND TELEVISION -- Ch07. Alfred Hitchcock -- Ch08. Heroes for Hard Times -- Ch09. Documenting Crime -- Ch10. Screening the Law -- PartIV. FILM, CRIME, AND THE SOCIAL WORLD -- Ch11. Race and Serial Killing in the Media -- Ch12. Globalization and the Rise of the Behemoth -- Ch13. A Depiction of Evil, Order, and Chaos -- PartV. PEDAGOGY, EPISTEMOLOGY, AND ETHICS IN FILMS OF LAW AND CRIME -- Ch14. Contours of a Cinematic Criminology -- Ch15. Fact, Fantasy, Fallacy -- Ch16. Tobias Beecher -- Ch17. Nationalities, Histories, Rhetorics -- Index -- About the Editorsand Contributors.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Law on television; Electronic books